THE EFFECT OF FINANCIAL COMPENSATION ON EMPLOYEE PERFORMANCE AT PT. BANK BTPN CABANG SUNGGUMINASA KABUPATEN GOWA - Eka Pradila Putra (Jurnal Ekonomi, 2021)
Financial compensation is one of several factors that can affect the level of employee performance. Compensation is an addition to the basic salary that is not expected by employees, but only part of it can be given, but only has certain achievements or certain skills and does not rebel when asked to complete it as soon as possible, such as reports or receipts that must be reported. This research was conducted using simple linear regression analysis, f test and t test to analyze the close relationship of 1 variable. The purpose of this study was to determine the effect of financial compensation on employee performance at PT. Bank BTPN Sungguminasa branch, Gowa Regency